2020
DOI: 10.1002/rmb2.12341
|View full text |Cite
|
Sign up to set email alerts
|

High stretch cycling inhibits the morphological and biological decidual process in human endometrial stromal cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…During infertility treatment, clinicians often assess the endometrium by transvaginal ultrasound and transabdominal ultrasound to evaluate endometrial receptivity. Assessing endometrial receptivity by ultrasound involves measuring various parameters, including endometrial thickness (EMT) [ 5 ], endometrial volume [ 6 ], endometrial pattern [ 7 ], and endometrial wave-like activity [ 8 ]. Most previous studies have focused on EMT and have revealed an association between an EMT of <7 mm and poor pregnancy outcomes [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During infertility treatment, clinicians often assess the endometrium by transvaginal ultrasound and transabdominal ultrasound to evaluate endometrial receptivity. Assessing endometrial receptivity by ultrasound involves measuring various parameters, including endometrial thickness (EMT) [ 5 ], endometrial volume [ 6 ], endometrial pattern [ 7 ], and endometrial wave-like activity [ 8 ]. Most previous studies have focused on EMT and have revealed an association between an EMT of <7 mm and poor pregnancy outcomes [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%